HUBUNGAN PARASOCIAL RELATIONSHIP, SENSE OF BELONGING DENGAN PSYCHOLOGICAL WELL-BEING PENGGEMAR K-POP GEN Z JAWA BARAT - Karmila Apriani; Rifqi Farisan Akbar; Pratidina Ekanesia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The development of digital culture and the globalization of popular culture have provided opportunities for Generation Z K-Pop fans to develop emotional connections, social identities, and attachment within fan communities. However, intensive involvement in fan culture may also influence individuals’ psychological conditions, particularly their psychological well-being. This study aims to analyze the relationship between parasocial relationship (PSR) and sense of belonging (SOB) on psychological well-being (PWB) among Generation Z K-Pop fans in West Java. This study employed a quantitative approach with a cross-sectional correlational design. The participants consisted of 107 individuals aged 18–29 years who actively participated in online K-Pop fan communities. Data were collected using the Celebrity Attitude Scale (CAS), Sense of Belonging Instrument (SOBI), and Scales of Psychological Well-Being (SPWB). Data analysis was conducted using multiple linear regression to examine the contribution of independent variables to psychological well-being. The results showed that parasocial relationship and sense of belonging had positive relationships and contributed to the psychological well-being of Generation Z K-Pop fans. Sense of belonging was found to have a more dominant role than parasocial relationship in explaining individuals’ psychological well-being. These findings indicate that stronger emotional attachment to idol figures and a higher sense of belonging within communities are associated with better psychological well-being among fans. This study supports Social Identity Theory and provides implications for developing more inclusive fan communities that are able to promote and maintain the psychological well-being of their members. ABSTRAK Perkembangan budaya digital dan globalisasi budaya populer telah memberikan ruang bagi penggemar K-Pop Generasi Z untuk membangun hubungan emosional, identitas sosial, serta keterikatan dalam komunitas penggemar. Namun, keterlibatan yang intens dalam budaya penggemar juga dapat memberikan pengaruh terhadap kondisi psikologis individu, khususnya dalam aspek psychological well-being. Penelitian ini bertujuan untuk menganalisis hubungan parasocial relationship (PSR) dan sense of belonging (SOB) terhadap psychological well-being (PWB) pada penggemar K-Pop Generasi Z di Jawa Barat. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional cross-sectional. Partisipan penelitian berjumlah 107 individu berusia 18–29 tahun yang aktif mengikuti komunitas penggemar K-Pop secara daring. Data penelitian dikumpulkan menggunakan Celebrity Attitude Scale (CAS), Sense of Belonging Instrument (SOBI), dan Scales of Psychological Well-Being (SPWB). Analisis data dilakukan menggunakan regresi linear berganda untuk mengetahui kontribusi variabel independen terhadap psychological well-being. Hasil penelitian menunjukkan bahwa parasocial relationship dan sense of belonging memiliki hubungan positif serta berkontribusi terhadap psychological well-being penggemar K-Pop Generasi Z. Sense of belonging ditemukan memiliki peran yang lebih dominan dibandingkan parasocial relationship dalam menjelaskan psychological well-being individu. Temuan ini menunjukkan bahwa semakin kuat keterikatan emosional terhadap figur idola dan semakin tinggi rasa memiliki terhadap komunitas, maka semakin baik kondisi kesejahteraan psikologis penggemar. Penelitian ini mendukung Social Identity Theory serta memberikan implikasi bagi pengembangan komunitas penggemar yang lebih inklusif dan mampu mendukung kesejahteraan psikologis anggotanya.